The evolution of mature cystic teratomas of the ovary into squamous cell carcinoma: two case reports and review of the literature. (4th July 2022) - Ziadeh, Hanane; Duforestel, Thierry; Bouredji, Kenza; Re, Daniel; Debono, Laurence; Zreik, Tony; Moufawad, Graziella; Ghaname, Wadih
Abstract: Mature Cystic Teratomas (MCT) of the ovary or Dermoid Cysts are common benign tumours found in 10–20% of women. However, 0.2–2% of those cysts underwent malignant transformation. Squamous Cell Carcinoma (SCC) is the most frequent histological type reported in the literature.As 2021, there are limited reports of malignant tumours arising from MCT with no guidelines related to the management of these atypical cases. Herein, we describe two cases of MCT that evolved into SCC with different stages and prognosis and we review the current literature to date highlighting the potential risk of malignant transformation of these considered benign cysts and the need for strong evidence protocols for staging and treatment of this atypical entity. IMPACT STATEMENT: What is already known on this subject? Mature Cystic Teratomas are found in 10-20% of women. However, a malignant behavior is observed in 2% of cases. What do the results of this study add? Our paper will describe two cases of malignant transformation of dermoid cyst in an effort to highlight the possible malignant risk of this entity and the need for specific management guidelines. What are the implications of these findings for clinical practice and/or further research? The prognosis of this converted cyst is very poor. By elaborating a standard management protocol for this tumour and operating every large cyst (>10 cm) in postmenopausal women, we may prevent this event.